Reproducibility of a Parkinsonism‐related metabolic brain network in non‐human primates: A descriptive pilot study with FDG PET. Issue 9 (August 2015) - Ma, Yilong; Johnston, Tom H.; Peng, Shichun; Zuo, Chuantao; Koprich, James B.; Fox, Susan H.; Guan, Yihui; Eidelberg, David; Brotchie, Jonathan M.
Abstract Background We have previously defined a parkinsonism‐related metabolic brain network in rhesus macaques using a high‐resolution research positron emission tomography camera. This brief article reports a descriptive pilot study to assess the reproducibility of network activity and regional glucose metabolism in independent parkinsonian macaques using a clinical positron emission tomography/CT camera. Methods [18F]fluorodeoxyglucose PET scans were acquired longitudinally over 3 months in three drug‐naïve parkinsonian and three healthy control cynomolgus macaques. Group difference and test–retest stability in network activity and regional glucose metabolism were evaluated graphically, using all brain images from these macaques. Results Comparing the parkinsonian macaques with the controls, network activity was elevated and remained stable over 3 months. Normalized glucose metabolism increased in putamen/globus pallidus and sensorimotor regions but decreased in posterior parietal cortices. Conclusions Parkinsonism‐related network activity can be reliably quantified in different macaques with a clinical positron emission tomography/CT scanner and is reproducible over a period typically employed in preclinical intervention studies. This measure can be a useful biomarker of disease process or drug effects in primate models of Parkinson's disease. ©2015 International Parkinson and Movement Disorder Society